Kualitas Dan Daya Simpan Ikan Bandeng Menggunakan Konsentrasi Daun Sirih Hijau Dan Lama Perendaman Yang Berbeda - PUJI LESTARI, Heni; , Dra. Titik Suryani, M.Sc (2016)
Milkfish s one of the farmed fish that live in brackish water and is a food that contains enough nutrients and beneficial for the body, namely the nutrient content of milkfish content 70.7%; ash content of 1.4%; protein 24.1%; lipid 0.85%; carbohydrates 2.7%. Nonperishable milkfish will require preservation. Natural preservative that is anti-bacterial properties of green betel leaf. Green betel leaves contain essential oils 0.8-1, 8% and amino acids that serve as antimicrobial, The purpose of this study on the abundance of bacteria, pH, water content, the physical quality and shelf life of milkfish. Plan this study using completely randomized design (CRD) with two factors: factor 1: concentration of betel leaf green 5% (S1), 10% (S2), 15% (S3) and a factor of 2: soaked for 30 minutes (L1), 60 minutes (L2). the results showed the quality of fish the best in treatment S3L2 ( 15% green betel leaf and soaked 60 minutes) with the number of bacteria 1,23x107 CFU / g, a pH of 5.8 and a water content of 47.3% and result sensory test and storability of the best after 18 hours on treatment S3L1 (green betel leaf 15 % and soaking time 30 minutes) the aroma is distinctive odor betel, prominent eyes, dense texture supple, bright pink gills and pale dull appearance.